Efeitos positivos da suplementação com farinha de folha de batata-doce biofortificada sobre o metabolismo, adiposidade e estresse oxidativo em ratos wistar machos - Sawazaki, Ellen Kayumi Mariano (2020)
Orange-fleshed Sweet Potato - OFSP, refers to one of the food crops obtained by biofortification. The study of the OFSP leaves can therefore expand its use and provide new elements with additional nutritional values for health promotion. The present study evaluated the effect of supplementing the flour obtained from the OFSP leaf on the adiposity and metabolic conditions of Wistar rats. The research has a basic experimental character, being performed with Wistar rats (n = 20) divided into Supplemented Group (n = 10), which received 2g of OFSP flour in 2mL of water via gavage, administered during 6 weeks. Unsupplemented rats received the same volume of water without the flour. At 69 days old and after 12 hours of fasting, the rats were weighed, measured the nasoanal length to calculate the Lee index and collected whole blood for analysis of: glucose, blood count, lipid profile and total antioxidant capacity TAC. The histology of the adipose and hepatic tissue was performed. The data are presented as mean ± standard error of the mean (SEM). Student‟s t-test for normal distribution. P <0.05 were considered statistically significant. As main results, lower weight and lower adipocyte volume were obtained in visceral fat and there was a reduction in VLDL-cholesterol in the Supplemented Group. It can be concluded that the OFSP leaves have anti-inflammatory properties, expressed in the reduction in the lipid profile and reduction of the accumulation of fat in the adipocytes. These effects correlate with combating free radicals and preventing damage related to oxidative stress, such as NCDs.